2021
DOI: 10.1016/j.scitotenv.2021.148951
|View full text |Cite
|
Sign up to set email alerts
|

Plastic waste footprint in the context of COVID-19: Reduction challenges and policy recommendations towards sustainable development goals

Abstract: The sudden surge in demand to use plastic products due to COVID-19 pandemic has increased plastic pollution. It has resulted into degradation of a broad range of habitats and ecosystems by destroying natural functions, water quality, and environmental sustainability. However, the government agencies, scientific communities, and the public, have started to give attention to this issue. So, in the present study, we used the correlation methods to check the relationship between COVID-19 affected population with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…The study by Olaifa et al., (2018) supports this argument. It was revealed in their study that in order to increase awareness on the proper disposal of DMs among people, then there is a need to continue educating them in whatever platforms ( Das et al., 2021 ; Mallick et al., 2021 ; Parashar and Hait, 2021 ) and regardless of their demographics. The information to be shared to continuously educate people on proper DM disposal should include the composition of DMs, hazards associated with improper disposal, and proper and safe ways to dispose these.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study by Olaifa et al., (2018) supports this argument. It was revealed in their study that in order to increase awareness on the proper disposal of DMs among people, then there is a need to continue educating them in whatever platforms ( Das et al., 2021 ; Mallick et al., 2021 ; Parashar and Hait, 2021 ) and regardless of their demographics. The information to be shared to continuously educate people on proper DM disposal should include the composition of DMs, hazards associated with improper disposal, and proper and safe ways to dispose these.…”
Section: Resultsmentioning
confidence: 99%
“…Toward a sustainable approach in improving the knowledge and practices of Filipinos in the proper disposal of plastic wastes, such as used DMs, the education sector should plan and design curriculum spaces for the inclusion of environmental education. Empowering people in order to reinforce and sustain a certain environmental operation is a necessary action to bring about successful participatory implementation ( Das et al., 2021 ; Limon and Villarino, 2020 ; Limon et al., 2020 ; Mallick et al., 2021 ; Parashar and Hait, 2021 ). The use of color-coded or labelled waste bags or bins in households, medical and health facilities, isolation and quarantine areas, and in local government units must be practiced in order to avoid littering and mismanagement of used DMs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning SDG 12, a large amount of food is lost in the supply chain before reaching the end customer. The upheaval of biomedical waste generation is witnessed during the pandemic, especially the single-use plastic products (such as PPE) (Mallick et al 2021 ). Regarding plastic pollution, a study found that there is a strong correlation between COVID-19-affected population and plastic waste footprint.…”
Section: Pandemic—a Distinctive Drag On Un Sustainable Development Goalsmentioning
confidence: 99%